An Expert System for Trouble Shooting - Auto Wire Bonder Machine - Ng, Yu Ting (1997)
An expert system to trouble shoot auto Wire bonder machine has been developed at Dpak product line, Motorola Semiconductor Sdn. Bhd., Seremban. This expert system is to provide a systematic and analytical procedure to trouble shoot Delvotec 6830 auto wire bonder. A rule-based expert system using backward chaining method is developed to guide the user during trouble shooting wire bond defect. The expert system collects information from the user on the wire bond defects by asking various questions. When the expert system reached to a conclusion, the recommend adjustment procedure and corrective action will be shown on the Pc. This expert system, running on a personal computer (PC), is programmed using Vp- Expert Shell, it captures the domain expert knowledge in wire bonding process into the knowledge base. Knowledge for this system is elicited from the domain expert through interviews and discussion, other sources of knowledge are from manufacturer operating manual, Total control Methodology CTCM) file and literature. The aid of this expert system is to improve bonding quality by reducing production yield loss.